PERBEDAAN KECERDASAN EMOSI REMAJA DENGAN STATUS PEKERJAAN IBU SEBAGAI TKW DAN NON TKW - Nur Aini; Avina Cahyaning Wahyu; Zaqqi Ubaidillah (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
Working as a female migrant worker has a positive and negative impact. Negative impacts include children who are left without love, this will cause children to experience intellectual, emotional and moral social problems. The purpose of this study was to determine the differences in emotional intelligence of teenagers with the employment status of mothers as migrant workers and non-migrant workers. Method used comparative descriptive research design with cross sectional approach. Sample was 31 teenagers with mothers of migrant workers and 30 teenagers with non-migrant mothers was taken by purposive sampling technique. The study was conducted at Nurul Huda and Mambaul Ulum Islamic junior high school, and also junior high public school 1 Bantur in September 2017. The dependent variable was emotional intelligence, measured by the TEIQue-ASF questionnaire (Trait Emotional Intelligence Questionnaire Adolescent Short Form). Data analyzed by independent t test. The average value of emotional intelligence in teenager with mothers of migrant worker is 129.03, in teenager with non migrant workers is 141.53. P value (0.005) < α (0.05), meaning that there are differences in emotional intelligence in both teenagers, where in teenager with non migrant worker their emotional intelligence is higher. Parental attachments, especially mothers can influence emotional response patterns, so this will affect emotional intelligence. It is recommended to the school to monitor emotional intelligence, because it can have an impact on their social behavior and conduct direction to surrogate family members who work as migrant workers about how to educate children in their teens. Keywords : Emotional Quotient, teenager, Mother Migrant Workers, Mother Non Migrant Workers